Preparation, characterization and evaluation of capsaicin-loaded indica rice starch nanoparticles. (30th August 2022) - Tao, Xiaoqi; Zhan, Lei; Huang, Yanxia; Li, Pan; Liu, Baona; Chen, Pei
Highlights: Indica rice starch nanoparticles (IRSNPs) were used for loading capsaicin (CAP). Some chemical interactions between IRSNPs and CAP were elucidated. IRSNPs delayed release of CAP in 50% ethanol solution, PBS of pH 1.2 and of pH 7.0. The CAP concentration, diffusion and matrix erosion might impact CAP release from CAP-IRSNPs. Abstract: Capsaicin (CAP) is an alkaloid with multiple physiological effects, but its application is difficult. In this research, indica rice starch nanoparticles (IRSNPs) based nanocarrier was used to load CAP to obtain capsaicin-loaded indica rice starch nanoparticles (CAP-IRSNPs). The microstructure, characteristics and in vitro release behaviors of CAP-IRSNPs were analyzed. CAP-IRSNPs presented average particle sizes of 617.84 ± 6.38 nm, encapsulation efficiency of 70.05 ± 1.78% and loading capacity of 13.41 ± 0.18%. Fourier-transform infrared spectroscopy confirmed that CAP-IRSNPs might be formed by hydrogen-bonding action. Differential scanning calorimetry and X-ray diffraction showed that IRSNPs influenced the crystallization and melting temperatures of CAP. In in vitro release study, CAP-IRSNPs exhibited a sustained release. The CAP concentration, CAP diffusion from matrix and matrix erosion might be the potentially possible mechanisms for capsaicin release from CAP-IRSNPs. These new results concluded that IRSNPs may be a promising nanocarrier for CAP or other hydrophobic bioactive ingredients.